2010
DOI: 10.1039/b927369g
|View full text |Cite
|
Sign up to set email alerts
|

Responsive microcapsule reactors based on hydrogen-bonded tannic acid layer-by-layer assemblies

Abstract: We explore responsive properties of hollow multilayer shells of tannic acid assembled with a range of neutral polymers, poly(N-vinylpyrrolidone) (PVPON), poly(N-vinylcaprolactam) (PVCL) or poly(N-isopropylacrylamide) (PNIPAM). We found that properties of the nanoscale shells fabricated through hydrogen-bonded layer-by-layer (LbL) assembly can be tuned changing the interaction strength of a neutral polymer with tannic acid, and by a change in counterpart hydrophobicity. Unlike most hydrogen-bonded LbL films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
236
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(258 citation statements)
references
References 95 publications
18
236
2
2
Order By: Relevance
“…The appearance of a new band at 2632 cm -1 in the spectra of the multilayer, which is assigned to N-H stretching vibrations, also indicates the formation of intermolecular hydrogen bonds. On the other hand, the bands appearing in the 3180-3400 cm -1 spectral region are identified as the O-H stretching bands for the phenolic groups [22,30]. It can be also noticed that the absorption band of the hydroxyl groups in the TAN shifts from 3334 to 3280 cm -1 (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The appearance of a new band at 2632 cm -1 in the spectra of the multilayer, which is assigned to N-H stretching vibrations, also indicates the formation of intermolecular hydrogen bonds. On the other hand, the bands appearing in the 3180-3400 cm -1 spectral region are identified as the O-H stretching bands for the phenolic groups [22,30]. It can be also noticed that the absorption band of the hydroxyl groups in the TAN shifts from 3334 to 3280 cm -1 (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, tannin coatings can exhibit antibacterial, antimutagenic or antimicrobial effects [18][19][20]. There has also been an increasing interest in H-bonded assembly of tannic acid with several neutral polymers, including poly(Nvinylpyrrolidone), for the development of physiologically stable thin films and hollow capsules for controlled drug release (since tannin can be a model polyphenolic drug) and other biotechnology applications [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The disparity in shell thickness may be ascribed to the different molecular weight of various PPs. 27 This demonstrated the general applicability of this method in the engineering of Au-based coreshell catalysts.…”
Section: -24mentioning
confidence: 88%
“…It was shown in Figure 6a−e that there was no apparent boundary between the active layer and the support layer, which could be ascribed to the infiltration of coating solution into the nanopores of support layer. Figure 6f showed that the membrane thickness exhibited a rapid growth 12,13 and increased from 43 nm to 171 nm with the bilayer number increasing from 0.5 to 5.5. A similar result was also obtained in the LbL self-assembly of epigallocatechin gallate (EGCG) with gelatin (Type A).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…10 With the development of LbL self-assembly technique, diverse functions and properties are often demanded for multilayer films, which require a broader range of components beyond charged species. As a result, constructing multilayer films on the basis of non-electrostatic interactions such as hydrophobic interaction, 11 hydrogen bond, 12,13 and metal−ligand coordination 6,9 has gained more and more attention. 8 Hydrophobic interaction refers to the interaction formed between hydrophobic groups in an aqueous environment under enthalpy effect and entropy effect, which makes the hydrophobic groups cluster to reduce their exposure to water molecules.…”
Section: ■ Introductionmentioning
confidence: 99%